MANAJEMEN INVESTASI UNTUK MENINGKATKAN KEKAYAAN PAK TAJIRUDIN - , Danang Prabowo Aji ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This thesis discusses the wealth management of a client named Tajirudin (name suppressed). By knowing the client type of risk-taking profile, the author analyze and evaluate the management of wealth thus formulate alternative solutions based on investment management and client risk tolerance. Client problems in his wealth management is mainly the lack of knowledge in investment management. Client assets is less diversified, which most comprised of homes and land assets. Clients have a conservative risk tolerance. Client's financial goal is to increase the wealth and net cash flow. Besides, clients also want to prepare a wedding fund for his two children. To meet the client's goals, the author recommends two alternatives investment management. Both alternatives are implemented firstly by doing rebalancing in client assets. The results of rebalancing activities are invested into other assets that have not owned by the client yet. The results of the two alternatives differ in which each has advantages and disadvantages. Both of these alternatives are able to meet client's financial goals. Clients choose the second alternative because it is able to meet client's financial goals and give convenience for clients